Arduino Uno Based Automatic Fruit Maturity Detection System for Orange (Citrus sp.) and Bell Fruits (Syzygium aqueum) Using Electrical Conductivity - Ummah, Auliya Rahmatul; Fitriani, Ade; Nur Hanafi, Kholis; Syahrir, Syahrir; Supriyanto, Supriyanto; Zarkasi, Ahmad (Lontar Physics Today, 2025)
Accurate determination of fruit ripeness is essential to maintain product quality, flavor, and market value. However, traditional manual assessment methods, which rely on sensory observation (color, aroma, and texture), are often subjective and inconsistent. This study aims to design and develop an automatic fruit ripeness detection system based on electrical conductivity measurement in oranges and bell fruits. The system utilizes a three-electrode stainless steel needle probe connected to an ADS1115 Analog-to-Digital Converter (ADC) module and an Arduino Uno microcontroller. A refractometer was used for system calibration and reference data acquisition. Measurements were performed by inserting the probe into the fruit pulp to read the voltage value of the fruit's fluid. This electrical signal was correlated with the reference sugar content (%Brix) and subsequently classified into three categories: ripe, half-ripe, and unripe. Results show that the average voltage range for oranges in the ripe, half-ripe, and unripe categories was 2.74 V, 2.58 V, and 2.32 V, respectively. For bell fruits, the corresponding voltage ranges were 2.48 V, 2.26 V, and 2.08 V. These voltage values were derived from the experimental data presented in Table 1 and  Table 2. The abstract  reports the average voltage for each ripeness category, whereas the tables list individual measurement values, resulting in slight differences between the summarized and detailed data. The average relative error of the measurement was found to be approximately 5 %, which is considered acceptable for practical field application. This indicates that the developed system is capable of classifying fruit ripeness in a non-destructive, accurate, and rapid manner.